Brain PUFA Concentrations Are Differentially Affected by Interactions of Diet, Sex, Brain Regions, and Phospholipid Pools in Mice. Issue 12 (13th November 2020) - Chen, Chuck T; Haven, Sophie; Lecaj, Lea; Borgstrom, Mark; Torabi, Mohammad; SanGiovanni, John Paul; Hibbeln, Joseph R
ABSTRACT: Background: PUFAs play vital roles in the development, maintenance, and functioning of circuitries that regulate reward and social behaviors. Therefore, modulations in PUFA concentrations of these brain regions may disrupt reward and social circuitries contributing to mood disorders, developmental disabilities, and addictions. Though much is known about regional and phospholipid-pool-specific PUFA concentrations, less is known about the effects of dietary interventions that concurrently lowers n–6 PUFA and supplements n–3 PUFA, on brain PUFA concentrations. There is even less knowledge on the effects of sex on brain PUFA concentrations. Objective: This study aimed to comprehensively examine the interaction effects of diet (D), sex (S), brain regions (BR), and phospholipid pools (PL) on brain PUFA concentrations. Methods: Male and female C57BL/6J mice were fed 1 of 4 custom-designed diets varying in linoleic acid (LNA) (8 en% or 1 en%) and eicosapentaenoic acid/docosahexaenoic acid (EPA/DHA) (0.4 en% or 0 en%) concentrations from in utero to 15 weeks old. At 15 weeks old, the prefrontal cortex, dorsal striatum, and cerebellum were collected. Fatty acids of 5 major PL were quantified by GC-flame ionization detection. Repeated measures ANOVA was used to test for differences among the groups for D, S, BR, and PL. Results: No significant 4-way interactions on PUFA concentrations. DHA, predominant n–3 PUFA, concentrations were dependent on significant D × BR × PL interactions. DHA concentration was not affected by sex. Arachidonic acid (ARA; predominant n–6 PUFA) concentrations were not dependent on 3-way interactions. However, significant 2-way D × PL, BR × PL, and D × Sinteractions affected ARA concentrations. Brain fatty acid concentrations were differentially affected by various combinations of D, S, BR, and PL interactions. Conclusion: Though DHA concentrations are not affected by sex, ARA concentrations are affected by interactions of the 4 variables examined. This study provides comprehensive references in the investigation of complex interactions between factors that affect brain PUFA concentrations in mice.